Three solutions for the compensation problem. - Fleurbaey, Marc (Journal of Economic Theory, 1995)
The writer presents a model of fair division in which differential claims are based on talents and handicaps in order to examine the methods by which partial compensation can be performed in the context of a pure exchange economy in which a one-dimensional resource has to be divided among a finite population. It is demonstrated that the first two solutions, conditional equality and egalitarian-equivalence, demonstrate dual properties and that the consistency axiom has strong consequences in one-good models.